The Institute of Medicine's call to action revisited: assuring access to public health education for U.S. college students - Rosemary M. Caron; Semra Aytur; Haylee Foster (Frontiers Media S.A., 2023)
The Educated Citizen and Public Health initiative promotes that an understanding of public health issues is a principal component of an educated population and is necessary to develop social responsibility and promote civic dialog. This initiative supports the Institute of Medicine's (now the National Academy of Medicine) recommendation that "all undergraduates should have access to education in public health." The purpose of our work is to examine the extent to which 2- and 4-year U.S. state colleges and universities offer and/or require a public health course. Select indicators identified include the presence and type of public health curriculum, public health course requirement, presence of public health graduate program offering, pathways to public health, Community Health Worker training, as well as demographic information for each institution. An analysis was also conducted for the historically Black colleges and universities (HBCUs), and the same select indicators were examined. The data suggest that there is an imperative need for a public health curriculum across the nation's collegiate institutions with 26% of 4-year state institutions lacking a full undergraduate public health curriculum; 54% of 2-year colleges not offering a pathway to public health education; and 74% of HBCUs not offering a public health course or degree. In the age of COVID-19, syndemics, and considering the post-pandemic phase, we argue that expanding public health literacy at the associate and baccalaureate level can help prepare an educated citizenry who is both public health literate and one that can demonstrate resilience in the face of public health challenges.